The impact of adult trauma triage training on decision-making skills at Emergency Departments in Kelantan Hospital / Siti Aishah Ghazali - Siti Aishah, Ghazali (2018)
The Emergency Department (ED) is a “front door” facility that provides emergency treatment and care in hospitals for various conditions and for trauma patients. Patients brought into the ED require a fast and precise triage process by healthcare providers (HCPs) in a dynamic environment. An accurate triage category is vital to ascertain the best impact for patients’ health and it is a very challenging task. Inaccurate triage decisions may cause unnecessary harm due to the deterioration of patients’ condition, long waiting hours, misuse of resources, patient dissatisfaction towards ED services and the professionalism of HCPs. Therefore, HCPs who perform triage need to equip themselves with knowledge and skills of triaging. The purpose of the study was to identify triage decision-making skills, accuracy of triage decisions, and the effectiveness of an educational intervention among HCPs working in EDs. The study was conducted in the EDs of ten hospitals in Kelantan State, Malaysia. The study has three phases: Phase 1 was a cross-sectional, baseline study that provided pre-test data for 202 participants recruited from ten EDs using universal sampling. Phase 2 involved the development of an educational module on triage for adult trauma patients. Phase 3 was an interventional study, with the educational module as the intervention, and a randomized controlled trial design, followed by a two weeks (post-test) and four weeks interval (follow-up test) as measurements. The hospitals that obtained low Triage Decision Making Inventory (TDMI) scores were randomly allocated to a control group and an intervention group. The intervention group (69 participants) was exposed to the educational intervention that completed in 140 minutes, while no intervention was given iv to participants in the control group (74 participants), the TDMI and Patient ScenarioBased Questions (PSBQs) for adult trauma patients were used to measure triage decision making skills and accuracy of triage decisions for participants of both groups in the post-test and follow-up test, after the intervention group was exposed to the educational intervention. The results showed, 70.8% participants had summative TDMI score of less than 184 (mean =175; SD=20.21). For PSBQs, 69.8% scored a low accuracy of triage decisions (mean=10.52; SD=1.71). Two weeks post intervention, 92.8% of participants in the intervention group produced good scores for TDMI (mean=207.80a ; SE=1.85), compared to only 45.9% in the control group (mean=181.13a SE=1.76). Meanwhile, for the PSBQs test, 97.1% of participants in intervention group produced good scores for accuracy of triage decisions (mean=14.25a ; SE=0.18), compared to 16.2% in the control group (mean=9.64a ; SE=0.17). In the follow-up test, 81.2% of participants in the intervention group produced good scores for TDMI (mean=197.93a ; SE=2.44), compared to 43.2% in the control group (mean=178.07a ; SE=2.33) ; for the PSBQs test, 98.6% participants in the intervention group produced a good level of accuracy in triage decisions (mean=13.83a ; SE=0.19) compared to 9.5% in the control group (mean=9.48a ; SE=0.18). There was a significant effect for TDMI between the control group and intervention group (F(1,138) =60.72, p <.001, η 2 = .31), while for PSBQs the effect was (F(1,139) =270.31, p <.001, η 2 = .66) across time. There was an improvement of score for TDMI and PSBQs for intervention group after exposure to educational intervention across time.